2020
DOI: 10.3390/min10060552
|View full text |Cite
|
Sign up to set email alerts
|

Authigenic Carbonates in the Water–Biota–Bottom Sediments’ System of Small Lakes (South of Western Siberia)

Abstract: We studied 46 small, drainless lakes in various landscape types: The sub-taiga (Vasyugan plain), forest–steppe (Baraba lowland), and steppe and subzone of ribbon forests (Kulunda plain). Sampling of lake components (sediments, water, and biota) was performed. The materials were analyzed via a combination of modern analytical methods (atomic absorption spectroscopy, X-ray fluorescence, scanning electron microscopy and X-ray diffractometry). It was found that in the south of Western Siberia, lakes with a bicarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
1
10
1
Order By: Relevance
“…Differences in the biogeochemistry of sediments were revealed in a sharp increase in nitrogen in the system of lakes on the shores of which there are settlements. The material about of Corg, N and P in sediment of particular lakes have been shown in several articles [2,3,[24][25][26][27][28]. The importance of using the landscape approach in studying the processes of human relations with the geographical environment and the allocation of landscape macroregions has been discussed in the works of many authors.…”
Section: The Objectsmentioning
confidence: 99%
“…Differences in the biogeochemistry of sediments were revealed in a sharp increase in nitrogen in the system of lakes on the shores of which there are settlements. The material about of Corg, N and P in sediment of particular lakes have been shown in several articles [2,3,[24][25][26][27][28]. The importance of using the landscape approach in studying the processes of human relations with the geographical environment and the allocation of landscape macroregions has been discussed in the works of many authors.…”
Section: The Objectsmentioning
confidence: 99%
“…Small (<1 km 2 ) water bodies are strongly predominant in overall lake number. Most of the small lakes are saline, with overall mineralization higher than 1 g L −1 [6,7]. These lakes are of special interest, because these systems are very sensible to natural and human-induced changes in the climate and transformation of the landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of insoluble carbonate mineral formation in lakes is related to a number of parameters including geological and geomorphological context, the hydrochemical composition of waters, hydrological regime, biological activity, as well as the erosional processes within the watersheds [13]. Studies performed for large endorheic lake systems in different arid and semiarid regions of the world have shown that they are characterized by a high degree of intergroup variability in terms of sedimentation processes and authigenic mineral formation [7,[14][15][16][17][18][19][20][21][22][23][24][25]. These studies support the idea that the analyses of the role of endorheic lakes in the formation of regional terrestrial geochemical fluxes primarily requires an understanding of their morphometric diversity taking into account hydrochemical parameters and intensity of C sink in sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Small and large lakes, that significantly vary in terms of water chemistry and morphometric parameters are important components of the landscape mosaic in the arid and semiarid regions of Western Siberia and Northern Kazakhstan (Yermolayev and Wizer, 2010). A significant proportion of this water bodies is undrained and rather often saline (Ovdina et al, 2020), which results in the formation of specific aquatic and subaquatic ecosystems adjacent to such environments (Zarubina and Durnikin, 2005;Samylina et al, 2014). Another important feature of the lakes within the territory under consideration is related to the fact that they are very dynamic systems, subjected to significant seasonal, annual and decade-long fluctuations of water level (Meyer et al, 2008;Rudaya et al, 2012), that can result in their full drying off.…”
Section: Introductionmentioning
confidence: 99%